Penolakan Usulan Kabupaten Simalungun Hataran sebagai Pemekaran dari Kabupaten Simalungun - ALEX FERNANDO P SARAGIH (Universitas Sumatera Utara, 2016)
Structuring the region in accordance with Act No. 32 2004 is divided into two (2) concepts, namely the establishment of the area and the establishment of special zones. Which meant the formation regions, namely in terms of expansion and merging of regions.The formation of a special district that includes the creation of national strategic areas concerning the livelihood of the people in terms of political, social, cultural, environmental, defense and security, as well as the establishment of regional authorities, free trade, industrial estates and the like. This study examines the case of rejection the proposal to establish a new autonomous region of the district Simalungun Hataran as a division of Simalungun by (CoalitionRejected the Divisionof Kabupaten Simalungun/TPS). This study concluded that there are four important things to be the reason for rejection of the proposal SimalungunHataran by TPS. First, the imbalance in the management of the Regional Budget (APBD); Secondly, improper understanding concept the division; Third, the potential for ethnic conflict; Fourth, the burden of peverty. The method used is descriptive qualitative method that is intended to describe an event in more detail.Keywords: Autonomy, regional authorities, local politics.